COMPARATIVE DIGITAL ANALYSIS OF DIFFERENT PHENYTOIN CRYSTAL HABITS - FLÓREZ Ph.D., Oscar; TOBÓN Z. Ph.D., Gloria E.; VALENCIA V. Ph.D., Jaime A. (Vitae, 2012)
The purpose of this work was to evaluate the information obtained using some digital techniques for measuring the external form of pharmaceutical solids, employing a combination of several contour descriptors by means of classical and mathematics descriptors and a modified method of texture analysis technique based on Gray levels co-occurrence matrix. In this case, phenytoin was used as a model, because changing some conditions in the recrystallization process different crystalline habits were obtained. The evaluations of the measurements were performed using techniques of principal component analysis and hierarchical cluster analysis. Final analysis indicated that applying the texture technique Gray levels co-occurrence matrix measurement, the results were similar to those obtained by combining contour measurement with classical and mathematics descriptors techniques, therefore, as the texture method is faster and easier to implement, could be a good alternative for use in quality control of multisource pharmaceutical solid.